Frequency Control by Decentralized Controllable Heating Loads with H∞ controller - Yoshihisa Kinjyo; Kosuke Uchida; TomonobuSenjyu TomonobuSenjyu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Many isolated small power systems are powered by diesel generators, which results in greater operating costs than interconnected large grids. It is therefore desirable to integrate renewable energy sources such as wind power into these small grids. However, due to the fluctuating power generation from renewable energy sources, frequency deviations of power systems become problematic. Distributed intelligent load control can be used to significantly increase renewable energy penetration and cut diesel fuel consumption. This paper presents a methodology for grid frequency control by electric water heaters as controllable loads. This system consists of diesel generator, wind farm, and loads. By applying a power consumption controller adopted from H∞control theory, grid frequency deviation is maintained around rated value. In order to verify the effectiveness of the proposed system, MATLAB/Simulink is used for simulations.